Context-dependent change in the fitness effect of (in)organic phosphate antiporter glpT during Salmonella Typhimurium infection - Noemi Santamaria de Souza; Yassine Cherrak; Thea Bill Andersen; Michel Vetsch; Manja Barthel; Sanne Kroon; Erik Bakkeren; Christopher Schubert; Philipp Christen; Patrick Kiefer; Julia A. Vorholt; Bidong D. Nguyen; et al. (Nature Communications)
Abstract Salmonella enterica is a frequent cause of foodborne diseases, which is attributed to its adaptability. Even within a single host, expressing a gene can be beneficial in certain infection stages but neutral or even detrimental in others as previously shown for flagellins. Mutants deficient for the conserved glycerol-3-phosphate and phosphate antiporter glpT have been shown to be positively selected in nature, clinical, and laboratory settings. This suggests that different selective pressures select for the presence or absence of GlpT in a context dependent fashion, a phenomenon known as antagonistic pleiotropy. Using mutant libraries and reporters, we investigated the fitness of glpT-deficient mutants during murine orogastric infection. While glpT-deficient mutants thrive during initial growth in the gut lumen, where GlpT’s capacity to import phosphate is disadvantageous, they are counter-selected by macrophages. The dichotomy showcases the need to study the spatial and temporal heterogeneity of enteric pathogens’ fitness across distinct lifestyles and niches. Insights into the differential adaptation during infection may reveal opportunities for therapeutic interventions.